Cognitive neuroscience: emergence of mind from brain an introduction to the cognitive neuroscience series - McClelland, James (Henry Stewart Talks, 2013)
Cognitive neuroscience introduction, Basis of mental processes, Neurons and synapses, Synaptic integration and action potentials- Representation of information in neurons and populations of neurons, Processing of information in neural populations, Interactive processing, Macro organization of mental functions, Learning as adjustment of strengths of neuronal connections, What we know and what we don't know
Updated at 2020/07/08